Immunoglobulin Light Chain Gene Rearrangements, Receptor Editing and the Development of a Self-Tolerant Antibody Repertoire - Collins, Andrew M.; Watson, Corey T. (Frontiers in Immunology, 2018)
Discussion of the antibody repertoire usually emphasises diversity, but a conspicuous feature of the light chain repertoire is its lack of diversity. The diversity of reported allelic variants of germline light chain genes is also limited, even in well-studied species. In this review, the implications of this lack of diversity are considered. We explore germline and rearranged light chain genes in a variety of species, with a particular focus on human and mouse genes. The importance of the number, organization and orientation of the genes for the control of repertoire development is discussed, and we consider how primary rearrangements and receptor editing together shape the expressed light chain repertoire. The resulting repertoire is dominated by just a handful of IGKV and IGLV genes. It has been hypothesized that an important function of the light chain is to guard against self-reactivity, and the role of secondary rearrangements in this process could explain the genomic organization of the light chain genes. It could also explain why the light chain repertoire is so limited. Heavy and light chain genes may have co-evolved to ensure that suitable light chain partners are usually available for each heavy chain that forms early in B cell development. We suggest that the co-evolved loci of the house mouse often became separated during the inbreeding of laboratory mice, resulting in new pairings of loci that are derived from different sub-species of the house mouse. A resulting vulnerability to self-reactivity could explain at least some mouse models of autoimmune disease.